PERBANDINGAN EFEKTIVITAS EKSTRAK DAUN KERSEN (Mutingia calabura) DAN DAUN AKASIA (Acacia mangium) SEBAGAI LARVASIDA TERHADAP JENTIK NYAMUK Aedes aegypti (L.) DI WILAYAH BANJARMASIN: PERBANDINGAN EFEKTIVITAS EKSTRAK DAUN KERSEN (Mutingia calabura) DAN DAUN AKASIA (Acacia mangium) SEBAGAI LARVASIDA TERHADAP JENTIK NYAMUK Aedes aegypti (L.) DI WILAYAH BANJARMASIN - Hajrah Hidriya; Wulan Pertiwi; Yuliana Salman (LPPM Universitas Abdurrab, 2022)
Dengue fever (dengue) is a dangerous and even deadly disease caused by the Aedes aegypti mosquito as the vector of the disease. One way to prevent dengue fever (dengue) is the use of larvicides to inhibit and kill Aedes aegypti larvae. In this case, it is necessary to use one part of the plant, namely Kersen leaves (Mutingia calabura) and Acacia leaves (Acacia mangium). This study aims to compare the effectiveness of the effect of the bioactive compounds contained in extracts of Kersen leaves (Mutingia calabura) and Acacia leaves (Acacia mangium) as larvicides. The plant extraction method is simplicia. The prepared leaf samples were washed thoroughly and dried for Â± 2 weeks in a closed state from the sun. The dried leaf samples were then mashed with a dry blender to obtain powder (dry weight), then macerated with ethanol solvent with a concentration of 0.1%, 0.5% and 1%. Based on the results of the research conducted, there was a significant effect of giving cherry leaf extract and acacia leaves from each concentration tested after 24 hours of treatment, with the highest number of larvae deaths at a concentration of 1%. However, in this case there was no significant difference between the administration of the two extracts as Aedes aegypti larvicide